KONTRAK PENGELOLAAN DANA BERBASIS REPURCHASE AGREEMENT (REPO) SAHAM - Welin Kusuma, 030810236 N (2009)
The title of this thesis is Stock Repurchase Agreement Based Discretionary Fund Contract. The objective of this research is to analyze contractual relationship between the parties and risk types of stock repurchase agreement based discretionary fund contract. The type of this research is a legal research. In this research, statute approach and conceptual approach are employed. From this research, two things are found. First, investment manager makes agreement with investors to place fund in stock repurchase agreement instrument whereupon investment manager as buyer of stock repurchase agreement makes agreement with stock repurchase agreement seller to buy and sell shares with the right to sell back. Second, risk types of stock repurchase agreement based discretionary fund contract are legal risk, market risk, liquidity risk, and other risks. It is recommended in this thesis that before signing a stock repurchase agreement based discretionary fund contract, investors first need to read and understand the contents of the contract, while the investment manager must understand the contents of the contract in order to do its job well.